The Effect of Waiting Time for Doctor's Services on Patient Satisfaction in the Outpatient Department of RSUD Toto Kabila - Fuji Fauzia H. Yakop; Titin Dunggio; Serly Daud (LPPM Universitas Bina Mandiri Gorontalo, 2021)
This study aims to determine the effect of waiting time for doctor's services on patient satisfaction in the Outpatient Department of RSUD Toto Kabila. This study aims to determine whether there is an effect of waiting time for doctor's services on patient satisfaction in the outpatient department of RSUD Toto Kabila which is seen from the waiting time and the five